The Effects of Community Size, Control Over Agenda, and Contextual Variables on Zika Virus Preparation of Public Information Offi cers at Local Public Health Departments (Journal of International Crisis and Risk Communication Research, 2019)
As Zika emerged as a major global health threat, public information offi cers (PIOs) at local public health departments across the United States prepared for outbreaks of the virus amid great uncertainty. Using the crisis and risk emergency communication (CERC) model to inform this study, PIOs (n = 226) at public health departments were surveyed to assess how community size, perceived control over health agenda, and other considerations such as resources and federal infl uences aff ected their satisfaction with Zika preparedness in their departments. These contextual, indirect factors may moderate planning eff orts for Zika and other health emergencies and thus should be considered in crisis management and planning models such as CERC.